1999
DOI: 10.1021/jf981249r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salts on the Gelatinization and Rheological Properties of Sago Starch

Abstract: The effects of various salts on the gelatinization and rheological properties of sago starch have been studied using differential scanning calorimetry, small deformation oscillation, and large deformation techniques. The presence of salts affected the gelatinization peak temperature, T(p), gelatinization enthalpy, DeltaH, swelling properties, storage modulus, G', gel strength, GS, and gelation rate constants, k, depending on the type of salt and the concentration. Their influence followed the Hofmeister series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(74 citation statements)
references
References 29 publications
5
67
1
1
Order By: Relevance
“…The halogen ion of the sodium salt also affected the a value in the order of NaCl < NaBr < NaI. These orders are in reverse to the Hofmeister (lyotropic) series, [9][10][11][12] where Li þ > Na þ > K þ for alkaline metal ions with the same anion counterpart and Cl À > Br À > I À for halogen ions coupled with a constant cation. Figure 3 also shows the temperature dependence of the initial sorption rates in water and in the 1.83 mol/L NaCl solution.…”
Section: Resultsmentioning
confidence: 99%
“…The halogen ion of the sodium salt also affected the a value in the order of NaCl < NaBr < NaI. These orders are in reverse to the Hofmeister (lyotropic) series, [9][10][11][12] where Li þ > Na þ > K þ for alkaline metal ions with the same anion counterpart and Cl À > Br À > I À for halogen ions coupled with a constant cation. Figure 3 also shows the temperature dependence of the initial sorption rates in water and in the 1.83 mol/L NaCl solution.…”
Section: Resultsmentioning
confidence: 99%
“…The DSC results of this chapter ( Generally, gelatinization is a heat based transformation, yet, it is also known that starch gelatinization is affected by various salts and some salts result in starch gelatinization at room temperature (Jane, 1993;Ahmad & Williams, 1999). The ability of some salts to gelatinize starch at room temperature rests on two effects according to Jane (1993) reversed again (very similar to results of this study) but with an exothermic peak at a higher temperature than the previous one.…”
Section: Ftir Spectroscopysupporting
confidence: 84%
“…An interesting point also noted in the Sciarini et al (2014) study is the exothermic-endothermic peak developed at the 70 % CholAc. At room temperature, Ahmad & Williams (1999) also reported that sago starch gelatinized at a concentration of 3.5 M for MgCl 2 . Although no report is given by Sciarini et al (2014) on the effect of CholAc solutions at room temperature, from the reported portion, it is very likely that the CholAc can also gelatinize regular corn starch at room temperature.…”
Section: Ftir Spectroscopymentioning
confidence: 88%
“…An increase in starch and fiber crystallinity is attributed to preferential hydrolysis of the amorphous domains by acid (Gerard et al 2002). Ahmad and Williams (1999) and Pukkahuta and Varavinit (2007) found that sago hampas has a crystallinity type between cereal (A-type) and tuber (B-type). The profiles also expressed the mixture of starch and fiber crystalline fractions.…”
Section: Slow Acid Hydrolysismentioning
confidence: 99%
“…Sago starch has been used for a long time, especially in Southeast Asia in the food industry for the production of sago pearl, vermicelli, bread, cake, biscuits, and many other traditional foods (Ahmad and Williams 1999). Sago palm (Metroxylon sp.)…”
Section: Introductionmentioning
confidence: 99%